1,2-Di-tert-butylmethylenphosphan und seine Addukte mit Aluminiumtrichlorid, Schwefel und Selen - Edgar Niecke; Erhard Symalla (CHIMIA)
Synthesis and spectroscopic data of a novel phosphaalkene, R–P=CH–R (2:R = C(CH3)3), are reported. With AlCl3 this phosphaalkene reacts to the Lewis acidbase adduct 7, while with sulfur and selenium it reacts to the three-membered ring compounds 8 and 9, respectively, via a nucleophilic attack at the π-system.